Ceroid-lipofuscinosis: ultrastructural study of 8 cases. - Matias, C (1989)
The authors studied the clinical and ultrastructural features of 8 cases of Neuronal Ceroid-Lipofuscinosis (NCL). Five cases of the late-infantile type and 3 cases of the juvenile type. The clinical diagnosis of all cases was confirmed by the electron microscopy analysis of the peripheral blood lymphocytes and biopsy material from the skin, palpebral conjunctiva, skeletal muscle and rectal mucosa. Our observations agree with previous reports concerning the predominance of curvilinear bodies in the cells of the late infantile type, and fingerprint-like structures in those of the juvenile type. The finding of parallel tubular arrays and NCL inclusions associated in the same lymphocyte (frequently in the same vacuole) suggests that those structures could be related to the metabolic error of NCL. Ultrastructural examination of microbuffycoats of peripheric blood lymphocytes is a simple, time-saving and reliable method that allows specific confirmation of a clinical diagnosis of Neuronal Ceroid-Lipofuscinosis.